The Use of the Case Method to Promote Reflective Thinking in Teacher Education - Liu, Wei-Yu; Chen, Pin (Advances in Social Sciences Research Journal, 2019)
This research introduces and reflects on the utilization of case study method in the field of teacher education to explore how case study method impacts students’ reflective thinking towards education issues. Over the duration of study, an action research was conducted in the Education Issue course of teacher education program in a National University. Two case videos and the following discussions were used as tools to enhance students’ reflective thinking towards the assigned issues. The result of this study shows that case study method might not alter students’ viewpoints, but it can surely enhance their degrees of reflective thinking on the assigned education issues.